Comparison of different weight-based scalars of remimazolam tosylate for anesthesia induction in obese patients: study protocol for a prospective, controlled trial - Wenwen Ni; Xiuwen Yi; Lili Feng; Yilei Shen; Jiali Jiao; Yirong Cai; Danyun Fu; Yuan Han; Ji’e Jia; Wenxian Li (Trials, 2023)
Abstract Background The physiologic and anthropometric characteristics changes associated with obesity may result in the alternation of pharmacologic management. Remimazolam tosylate is a new type of ultra-short-acting benzodiazepine with stable context-sensitive half-time (CSHT) and no lipid accumulation after long-time infusion. Although remimazolam tosylate has potential advantages for the induction and maintenance of anesthesia in obese patients, the appropriate induction dosing scalars among obese patients are unknown. Therefore, we aim to compare the different weight-based scalars for dosing remimazolam tosylate of anesthesia induction among obese patients. Methods/design The study will be performed as a prospective, single-center, double-blind, controlled clinical trial. The study design is a comparison of remimazolam tosylate requirements based on total body weight (TBW) or lean body weight (LBW) to reach a Modified Observer’s Assessment of Alertness and Sedation (MOAA/S) score of 0 among obese subjects (BMI ≥ 35 kg/m2). Another twenty normal-weight subjects (18.5 kg/m2 ≤ BMI < 25 kg/m2) will be enrolled as a control group, whose induction dose is scaled based on TBW. The infusion rate of remimazolam tosylate during induction is 12 mg/kg/h in all groups. Discussion Results of the present study will provide evidence of dose scalar of remimazolam tosylate to guide the clinical practice of anesthesia induction in obese patients. Trial registration Chinese Clinical Trial Registry ChiCTR220005664. Registered on 9 February 2022, https://www.chictr.org.cn/showproj.aspx?proj=151150 .